Case Study: Reaction Time of Children According to Age. (2017) - Bucsuházy, Kateřina; Semela, Marek
Abstract: Study presents findings of a simulator study that examined the differences of reaction time for children aged from 3 to 18 years, compared to adults aged from 20 to 30 years. Choice reaction time has been analysed and three sets of measurement have been realized. In the first set, psychical children's reaction time has been measured. Second experiment has contained the measurement of reaction time psychical with visual reaction time. All three components have been examined in the last experiment in sum. Obtained results have been statistically analysed using analysis of variance (ANOVA). Post hoc tests showed differences or similarities between selected age groups. Obtained results revealed a need to use other values of reaction time for children than for adults. Values of reaction time of adults can be possibly exchanged for a teenage, no significant differences between 15–18 and 20–30 age group have been found.